Laboratory studies of mathematical models thermal objects - Mygushchenko, Ruslan; Kropachek, Olga; Shustik, Liliia; Mygushchenko, Kateryna (Національний технічний університет "Харківський політехнічний інститут", 2022)
Is devoted to the development and analysis of mathematical models of thermal objects. The extruder adopted as a thermal object is a vivid example of multi-zone pass-through technological units, the value of which is enormous for the domestic economy. In the article, the replacement of a real industrial object with a laboratory sample is carried out to work out the methodology of practical identification when obtaining a mathematical model with its subsequent analysis. A positive result is able to transfer the obtained results to a real technological unit. In the article, the object of research was selected, possible representations of mathematical models of industrial objects were analyzed, methods of practical identification were reviewed, the method of practical identification of thermal objects was selected, a series of natural experiments was prepared in laboratory conditions and numerical results were obtained, numerical parameters of coefficients were determined transmission and transport delay of mathematical models, time constants of mathematical models were found, analysis of mathematical models of a laboratory installation from the angle of optimization was carried out. The obtained results made it possible to correctly approach the identification of the working zone of a multi-zone pass-through technological unit using the example of an extruder, which carries out the technological process of processing agricultural raw materials by separating product fractions. Namely, decide on the type of primary converter (temperature sensor), the location of the sensors on the object, evaluate the cross effects of the heating zones in statics, choose the structure and parameters of PI (proportional, integrating components) and PID (proportional, integrating, differential components) regulators to maintain the temperature specified by the technical task in the working area of the extruder.

Присвячена розробці та аналізу математичних моделей теплових об'єктів. В якості теплового об'єкту прийнятий екструдер з розділенням фракцій продукту – яскравий приклад багатозонних прохідних технологічних агрегатів, цінність якого для вітчизняного господарства величезна. В статті здійснене заміщення реального промислового об'єкту лабораторним зразком для відпрацювання методики практичної ідентифікації при отриманні математичної моделі з її наступним аналізом. Позитивний результат спроможний перенести отримані результати на реальний технологічний агрегат. В статті здійснений вибір об'єкта дослідження, проаналізовані можливі представлення математичних моделей промислових об'єктів, оглянуті методи практичної ідентифікації, здійснений вибір методу практичної ідентифікації теплових об'єктів, підготовлена серія натурного експерименту в лабораторних умовах та отримані чисельні результати, визначені чисельні параметри коефіцієнтів передачі та транспортного запізнення математичних моделей, знайдені сталі часу математичних моделей, здійснений аналіз математичних моделей лабораторної установки під кутом оптимізації. Отримані результати дозволили грамотно підійти до ідентифікації робочої зони багатозонного прохідного технологічного агрегату на прикладі екструдера, який здійснює технологічний процес переробки сільськогосподарської сировини шляхом розділення фракцій продукту. А саме визначитись з типом первинного перетворювача (датчика температури), місця розташування датчиків на об'єкті, оцінити перехресні впливи зон нагрівання в статиці, підібрати структуру і параметри ПІ (пропорційна, інтегруюча складові) та ПІД (пропорційна, інтегруюча, диференційна складові) регуляторів для підтримки заданої технічним завданням температури в робочій зоні екструдера.
Лабораторні дослідження математичних моделей теплових об'єктів
Keywords: practical identification; thermal object; temperature; sensor; mathematical model; Laplace transform; практична ідентифікація; тепловий об'єкт; температура; датчики; математична модель; перетворення Лапласа